Dietary Salt Intake is a Significant Determinant of Impaired Kidney Function in the General Population - Tomonori Sugiura; Hiroyuki Takase; Nobuyuki Ohte; Yasuaki Dohi (Karger Publishers, 2018)
Background/Aims: Kidney dysfunction is an important risk factor for cardiovascular disease and end-stage renal disease. This study investigated whether dietary salt intake predicts deterioration of kidney function in the general population. Methods: In all, 12 126 subjects with a normal estimated glomerular filtration rate (eGFR ≥60 mL/min per 1.73m2) attending an annual check-up were enrolled in the study and were followed-up for a median of 1754 days; the endpoint was the development of impaired kidney function (eGFR < 60 mL/min per 1.73m2). Individual salt intake was estimated using spot urine analysis. Results: At baseline, mean (± SD) salt intake and eGFR were 10.6 ± 3.4 g/day and 80.8 ± 12.9 mL/min per 1.73m2, respectively. During the follow-up period, 1384 subjects (25.2 per 1000 person-years) developed impaired kidney function. Multivariate Cox hazard regression analysis revealed salt intake as a significant predictor of the new onset of kidney impairment (hazard ratio 1.045; 95% confidence interval 1.025-1.065). Subjects were divided into two groups based on salt intake; the incidence of impaired kidney function was higher in the group with high than low salt intake (P < 0.001, log-rank test). Multivariate Cox hazard regression analysis indicated a 29% increased risk of developing impaired kidney function in the high-salt group. Multivariate linear regression analysis showed a significant correlation between salt intake and yearly decline in eGFR (β = 0.060, P < 0.001). Conclusion: Salt intake is associated with the development of impaired kidney function in the general population, independent of its effects on blood pressure. Salt restriction may help prevent the development of impaired kidney function.